PENGELOLAAN OBJEK WISATA PATUNG YESUS MEMBERKATI DI KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - PANURAT, ALFONSIUS; OGOTAN, MARTHA; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: Management in tourism or so-called tourism management is a series of actions planning, organizing,mobilization, and supervision undertaken to determine and achieve the targets that have been determinedthrough the utilization of human resources and other resources in the field of tourism. The tourism sector isone of the regional development sectors and has an important role in the economy either as a source of foreignexchange or income. Siau Tagulandang Islands District Biaro has a religious tourism object that is the Statueof Jesus Blessing which is strategically located in the coastal promontory of Balirangen Village, South EastSiau District which is managed by Tourism and Culture Office of Siau Tagulandang Biaro Regency. In aneffort to manage this object is faced with various problems such as the lack of awareness will treat existingtourist sites by polluting tourist areas such as littering, this is due to the availability of waste bins that are stilllacking to be placed in some places and the road to go to the location of the statue which is still not built andbeberaa visitor facilities that are not maintained and can not be used. Therefore, the focus of this research ison the management of the object of the statue of Jesus blessing in the district of Siau Tagulandang IslandsBiaro by using descriptive research method with qualitative approach which is analyzed by using managementtheory by George R. Terry namely Planning, Organizing, Actuating and Controlling. The result of the studyshows that the management of the object of Jesus statue in the district of Siau Tagulandang Islands Biaro isstill not optimal, because there are still problems found in the actions of Organizing and Controlling. Suggestionfrom researcher to government to pay more attention to management of this tourist object seriously andresponsible in order to remain become mainstay tour of society and icon of Sitaro Islands district.Keywords: Management, Tourism, Tourist Attraction